Uncommon progression of toxoplasmic papillitis: patient perception and case report - Elcio Luiz Bonamigo; Eglas Emanuel Rossi; Maria do Carmo Nunes da Rosa; Ricardo Alexandre Stock; Rodrigo Rosa Sampaio; Ronei Carlos Lora (Revista Brasileira de Oftalmologia, 2021)
ABSTRACT Ocular toxoplasmosis frequently presents as necrotizing retinochoroiditis and, less often, as peripapillary chorioretinitis and/or papillitis. The progression from papillitis to peripapillary retinochoroiditis has been rarely described. We report the case of a 52-year-old patient living in southern Brazil, who developed papillitis in the right eye and was treated with systemic corticosteroids (prednisone 0.6 mg/kg/day and pulse therapy with methylprednisolone 15 mg/kg/day, for 3 days). After 14 days, the patient developed peripapillary retinochoroiditis with vitritis and decreased visual acuity (20/60), and was immediately initiated on the classic oral treatment for toxoplasmosis, consisting of pyrimethamine (50 mg/day), sulfadiazine (4 g/day), folinic acid (15 mg every 3 days) and prednisone (0.6 mg/kg/day). The visual acuity of the right eye normalized after treatment (20/20), which lasted approximately 70 days, but scotomas were detected on visual field examination, especially in the lower nasal quadrant. Although two studies mentioned this presentation, our report emphasizes the possible manifestation of ocular toxoplasmosis as papillitis in the initial phase, with progression to peripapillary retinochoroiditis and permanent visual field defects, which justifies early treatment for toxoplasmosis in suspected cases, especially in endemic regions.